The Cultural Dynamism of Wong Ayeb and Wong Palembang in Kuto Batu - Misnawati, Desy; Fadhila, Lina; Candrasari, Yuli; Akmaluddin, Achmad (LPPM Universitas PGRI Sumatera Barat, 2023)
This study aims to describe and analyze the Palembang population, which consists of ethnic Chinese, Arabs, Javanese, and Malays. Cultural civilization occurs in Kuto Batu Village, also known as Pasar Kuto, inhabited by ethnic Palembang, Ayyeb, and Chinese ethnic. Conditions, nature, culture, religion, and social changes surrounding them are all mentioned in constructing reality. This study uses a descriptive qualitative research methodology, with data collected through observation, documentation, and interviews. Wong Ayyeb and Wong Palembang are community leaders who participated in this research. Data analysis in research includes data reduction, data display (presentation of data), and verification (concluding) which involves continuous verification activities during the study, namely since arriving at the research location, during data collection, and during the preparation of research results. The researchers used triangulation as an evaluation approach to determine the correctness of the data. Research findings regarding the process of interaction and communication, the residents of Kuto Batu Village cannot be limited by an identity that clearly distinguishes one culture from another. The urge to communicate is not limited to people who share the same cultural identity; however, the nature and extent of communication changed. Coexistence for decades resulted in many cultures assimilating and adapting into the two ethnicities' everyday lives. Recommendations in research the need for religious understanding of customs and culture in social rituals.